Aesthetic experiences in the Cerrado (Brazilian savanna): contributions to environmental education practice and research. Issue 9 (21st October 2017) - Iared, Valéria Ghisloti; Oliveira, Haydée Torres de; Reid, Alan
Abstract: In this paper, we reflect on a study in Brazil's Cerrado that attempts to address a lack of attention to an aesthetic dimension in environmental education practice and research. We start by tracing this lack to the overvaluing of the cognitive sphere in the educational process, noting its echo in the low aesthetic value attributed to the Cerrado biome. Then, through reflecting on an empirical, interview based study of sensations, perceptions and feelings evoked by aesthetic experiences in the Cerrado, we draw on insights from a hermeneutic phenomenological approach to identify key themes for environmental education research and practice in this regard. These include: recognising the singularity of experience; attending to the qualities of experience; acknowledging the value/s of 'lighter' and 'darker' experiences; and deepening emotions and verbal communication. In our final considerations, we discuss the limitations of the study, alongside new directions in studies of perception, experience, aesthetics and pedagogy that may also advance attention to an aesthetic dimension in environmental education practice and research.